Ranging behavior and potential for territoriality in equatorial sakis (Pithecia aequatorialis) in Amazonian Ecuador. Issue 4 (1st October 2018) - Van Belle, Sarie; Porter, Amy; Fernandez‐Duque, Eduardo; Di Fiore, Anthony
Abstract: Objectives: Territoriality refers to the consistent defense of an area within the home range (HR) against intrusions of conspecifics. It implies exclusive space use with low degree of overlap among neighboring groups, high site fidelity, specific ranging behavior such as high mobility relative to HR size and frequent visits of territory borders, and monitoring behavior. We examined ranging behavior and use of space to evaluate territoriality in Pithecia aequatorialis in Ecuador. Materials and methods: Between 2005 and 2015, we monitored one main study group continuously and five additional groups for shorter periods (5 months to 2.5 years) at the Tiputini Biodiversity Station, in eastern Ecuador. We scored the location of the study groups at 20 min intervals during, on average, 5 days per month. We estimated saki HRs and core areas (CAs) using the fixed kernel density method (95 and 50%, respectively). Results: The average HR size was 57 ha and the average CA 14 ha. The degree of overlap between HRs of neighboring groups was low (2–9%). For the main study group, the average overlap between annual HRs was 82%. Mean daily path length across groups was 1, 151 m; the defensibility index varied between 1.1 and 2.3 (values >1 are suggestive of territoriality), and the fractional monitoring rate varied between 0.06 and 0.15 (values >0.08 are suggestive of territoriality). Groups did not visit their HR borders (100 m inner buffer) more often than would be expected by chance. Travel speed and directness were comparable between the borders and the centers of groups' HRs. Discussion: Our multiyear study suggests that equatorial sakis show low degree of range overlap and high site fidelity and have the potential to be territorial, given their high mobility relative to HR size that allows for frequent border monitoring. Nevertheless, their movement patterns in border areas did not reveal evidence for monitoring behavior.